Unequal Alliance : The World Bank, the International Monetary Fund and the Philippines - Broad, Robin (Book collections on Project MUSE., 1988)
In this seminal work, U.S. development specialist Robin Broad chronicles the Philippine experiment with the structural adjustment model of development espoused by the World Bank and the International Monetary Fund.